“Real-Time” High-Throughput Drug and Synergy Testing for Multidrug-Resistant Bacterial Infection: A Case Report - Sun, Wei; Hesse, Shayla; Xu, Miao; Childs, Richard W.; Zheng, Wei; Williamson, Peter R. (Frontiers in Medicine, 2018)
Antibiotic management of infections with multidrug-resistant organisms (MDRO) represents a complex clinical challenge. We report here the first patient with a severe MDRO infection managed with assistance of a novel ‘real-time’ three-day high-throughput screen (HTS) that allowed screening of 9 drugs in 14 combinations in 2,304 total samplings. Identified synergies were used to modify patient therapy with the goal of reducing drug-induced toxicity. The desired clinical outcome was achieved on the HTS-informed therapeutic regimen, supporting the utility of HTS technology to expand standard antimicrobial susceptibility testing.